MO863: Electronic Patient Reported Outcome (EPRO) Collection in Dopps: Prospective Study Designed to Understand the Severity and Temporal Changes in Pruritus Symptoms in Hemodialysis Patients. (3rd May 2022) - Karaboyas, Angelo; Robinson, Bruce; Albert, Justin; Hogan, Anna; Kane, Lauren; Asgari, Elham; Guebre-Egziabher, Fitsum; Messa, Piergiorgio; Weinreich, Thomas; Walpen, Sebastian; Schaufler, Thilo; Pisoni, Ronald
Abstract: BACKGROUND AND AIMS: Chronic kidney disease-associated pruritus (CKD-aP) is often seen to affect 30–40% of hemodialysis (HD) patients, and baseline CKD-aP symptoms have been associated with worse quality of life, poor sleep quality, depression and survival. A need exists for documenting CKD-aP severity longitudinally via several CKD-aP instruments to allow for temporal evaluation of different domains of CKD-aP burden, and their relationships to other patient-reported outcomes (PROs). This will help to further inform the extent to which different domains of well-being are impacted by CKD-aP over time, and its variability across patients, for tailoring individualized clinical care of HD patients afflicted by CKD-aP. The Dialysis Outcomes and Practice Patterns Study (DOPPS) is an international prospective cohort of adult in-centre HD patients, with patients randomly selected from representative national samples of HD facilities. Many prior studies by DOPPS and others have used only a baseline measure of CKD-aP, which may underestimate the strength of the true associations with clinical outcomes. With more frequent data collection to update exposures and understand trajectories, we can better evaluate the extent to which CKD-aP is episodic versus chronic. We can also assess whether patients with more consistently severe CKD-aP have worse PROs than patients who are currently—but only recently—bothered by CKD-aP. These gaps in knowledge present an opportunity to undertake a prospective study to link longitudinal clinical data with focused and frequent capture of CKD-aP and PROs to better understand the prevalence, burden and management of CKD-aP from HD patients' perspectives. METHOD: This prospective electronic PRO (ePRO) study involves >100 HD units from the 7 European countries participating in DOPPS 7 (Belgium, France, Germany, Italy, Spain, Sweden, UK). The ePRO will be distributed at HD facilities at 3-month intervals during an 18-month data collection period from 2021–3. The ePRO will be offered to all patients enrolled in the DOPPS, yielding a potential sample of 2000–500 patients based on expected participation and return rates (∼67%). The ePRO data collection is focused on use of mobile (tablet, phone) devices used frequently by patients, but will also be operational on a desktop or laptop computer. Patients will use their personal device to scan a unique QR code, and typically complete the questionnaire while on site at their HD facility. The ePRO will include a combination of validated CKD-aP scales, general quality of life related instruments and healthcare resource utilization (HCRU), i.e. patient reported capture of itch medications and specialist visits known to the patient but not typically in the dialysis chart. A complete list of the ePRO components is shown in Table 1 . These ePRO data, together with linked longitudinal clinical data captured in DOPPS, will serve as the analytical basis for several planned research projects, including (i) comparing approaches to measure CKD-aP burden; (ii) describing within-patient trajectories of CKD-aP burden and associations with PROs; and (iii) CKD-aP and short-term outcomes including HCRU, hospitalization and mortality in the 3-months following each CKD-aP assessment. RESULTS: Data collection is underway as of August 2021, with initial data expected in early 2022. While not yet available, we expect to present preliminary descriptive data at the ERA-EDTA in May 2022. CONCLUSION: The community lacks longer-term, frequently captured data on pruritus severity and management in the HD setting. This DOPPS 18-month prospective ePRO will help address novel research questions investigating the longitudinal burden of pruritus from the patient perspective, using multiple validated instruments and relationships to PROs, clinical outcomes and healthcare resource utilization.